Gambusia holbrooki Survive Shear Stress, Pressurization and Avoid Blade Strike in a Simulated Pumped Hydroelectric Scheme - Doyle, Katherine E.; Ning, Nathan; Silva, Luiz G. M.; Brambilla, Eduardo M.; Boys, Craig A.; Deng, Z. Daniel; Fu, Tao; du Preez, Jan A.; Robinson, Wayne; Baumgartner, Lee J. (Frontiers in Environmental Science, 2020)
Pumped hydroelectric energy storage (PHES) projects are being considered worldwide to achieve renewable energy targets and to stabilize baseload energy supply from intermittent renewable energy sources. Unlike conventional hydroelectric systems that only pass water downstream, a feature of PHES schemes is that they rely on bi-directional water flow. In some cases, this flow can be across different waterbodies or catchments, posing a risk of inadvertently expanding the range of aquatic biota such as fish. The risk of this happening depends on the likelihood of survival of individuals, which remains poorly understood for turbines that are pumping rather than generating. This study quantified the survival of a globally widespread and invasive poeciliid fish, Eastern gambusia (Gambusia holbrooki), when exposed to three hydraulic stresses characteristic of those experienced through a PHES during the pumping phase. A shear flume and hyperbaric chamber were used to expose fish to different strain rates and rapid and sustained pressurization, respectively. Blade strike models were also used to predict fish survival through a Francis dual turbine / pump. Simulated ranges were based on design and operational conditions provided for a PHES scheme proposed in south-eastern Australia. All gambusia tested survived high levels of shear stress (up to 1853 s-1), extremely high pressurization (up to 7600 kPa gauge pressure) and the majority (> 93 %) were unlikely to be struck by a turbine blade. Given their tolerance to these extreme simulated stresses, we conclude that gambusia will likely survive passage through the simulated PHES scheme if they are entrained at the intake. Therefore, where a new PHES project poses the risk of inadvertently expanding the range of gambusia or similar poeciliid species, measures to minimize their spread or mitigate their ecosystem impacts should be considered.